2021
DOI: 10.3390/bios11100388
|View full text |Cite
|
Sign up to set email alerts
|

Microfluidic Lab-on-a-Chip Based on UHF-Dielectrophoresis for Stemness Phenotype Characterization and Discrimination among Glioblastoma Cells

Abstract: Glioblastoma (GBM) is one of the most aggressive solid tumors, particularly due to the presence of cancer stem cells (CSCs). Nowadays, the characterization of this cell type with an efficient, fast and low-cost method remains an issue. Hence, we have developed a microfluidic lab-on-a-chip based on dielectrophoresis (DEP) single cell electro-manipulation to measure the two crossover frequencies: fx01 in the low-frequency range (below 500 kHz) and fx02 in the ultra-high-frequency range (UHF, above 50 MHz). First… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 31 publications
1
22
0
Order By: Relevance
“…Functional near-infrared spectroscopy (fNIRS) is a state-of-the-art optical neuroimaging technique based on near-infrared biosensors that are used to identify stress levels. Physically, fNIRS has the advantage of being more accessible and convenient than other devices [ 9 , 10 , 11 , 12 ]. Additionally, brain hemodynamic responses acquired by fNIRS not only exhibit apparent differences between stressful tasks and rest states but also facilitate stress detection and diagnosis [ 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Functional near-infrared spectroscopy (fNIRS) is a state-of-the-art optical neuroimaging technique based on near-infrared biosensors that are used to identify stress levels. Physically, fNIRS has the advantage of being more accessible and convenient than other devices [ 9 , 10 , 11 , 12 ]. Additionally, brain hemodynamic responses acquired by fNIRS not only exhibit apparent differences between stressful tasks and rest states but also facilitate stress detection and diagnosis [ 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…When the frequency becomes higher, the electric field starts penetrating inside the cell, thus “probing” its content. For this reason, can be used to discriminate cells based on cytoplasm features [ 25 ], though, because of the technical difficulties associated with the high-frequency actuation and the high sensitivity of the DEP response to small cell variations within cell subpopulations, the separation of cells based on , generally referred to as ultra-high-frequency, UHF, DEP, has not been extensively explored as compared with low-frequency, -based, DEP.…”
Section: Dielectrophoresis: From Physics To Biological Applicationsmentioning
confidence: 99%
“…DEP can be applied for the detection of many sub-types of stem cells, including mesenchymal cells, neural stem cells, one marrow-derived mesenchymal stem cell, neural stem/progenitor cells and adipose tissue-derived stem cells [ 37 ]. However, for the sorting of CSCs, current DEP applications have been focused on glioblastoma stem cells (GBSCs) [ 25 , 38 ]. Interestingly, Lambert et al suggested that the expression of biological GBSCs markers and the measurement of the ultra-high-frequency crossover frequency f x 02 were closely linked [ 25 ].…”
Section: Dielectrophoresis: From Physics To Biological Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The lower permeabilization induced in U87 NS by the electric field could also depend on their specific intracellular dielectric characteristics. Indeed, the more differentiated tumor cells (U87 ML) can be identified and separated from the more undifferentiated stem subpopulation (U87 NS) on the basis of specific cytoplasmic redox characteristics [ 47 , 48 ] related to transmembrane proteins [ 47 , 48 , 49 ].…”
Section: Discussionmentioning
confidence: 99%